Variation of the water table and salinity in alluvial aquifers of underground dams in the semi-arid region of Rio Grande do Norte, Brazil (Bioscience Journal, 2019)
Despite the growing progress in the construction of underground dams, there are few studies to evaluate and monitor these reservoirs after their construction. Thus, a research study was carried out to evaluate the water table level in alluvial aquifers and water salinity in four underground dams selected in the Cobras river basin, Parelhas municipality, Rio Grande do Norte. Water level variation was monitored using the traditional method and the Ground Penetrating Radar with generation of 3D virtual models. Water samples were collected between the months of December 2010 and December 2011 for electrical conductivity analysis. The results indicate that the accumulation of groundwater and salinity (expressed by electrical conductivity) in the reservoirs were affected by the spatial position within the hydrographic basin (limited occurrence of alluvial aquifer recharge area in headwater sectors) and the presence of surface reservoirs (upstream dams), which promote a more continuous recharge, greater renovation, and reduction of the salinity of the waters of the alluvial aquifer downstream.